Cultural proximity in the adaptation of foreign TV dramas in Turkey: A comparative study on Anne and Bir Aile Hikayesi - Öztürk, Asiye (My University, 2019)
Following the phenomenal success of a number of European reality shows known as format programmes in late 1990s, a mania to locally adapt them began in many different parts of the world. A format which is created and broadcast in a specific location is a template of a programme that can be reproduced in new territories for new audiences. This led to a tremendous growth in the format trade industry. The growth of international format business heralded a new phase triggered by some early technological and structural transformations in the TV industry. However, the trend to adapt scripted TV formats such as comedy or drama TV series began much later due to a number of reasons. Most importantly, scripted TV series prove more challenging to adapt as they are culturally more sensitive. When a TV series is adapted for a new market, it is crucial that the adapted version find resonance with home audiences in order to be successful. The success of adapted TV series depends on whether audiences find cultural proximity in what they watch or not. This thesis will take cultural proximity which is a complex concept with diverse components as the main theory to analyse two TV series that are adapted for Turkish TV; Anne (Mother) and Bir Aile Hikayesi (This is Us). While cultural proximity focuses on certain aspects that make an adapted TV series more relevant and proximate to home audiences, some other aspects ignored by the proponents of cultural proximity come into play. Therefore, factors that cultural proximity is built upon and some other factors that cultural proximity overlooks will be analysed regarding two adapted TV series: Anne (Mother) and Bir Aile Hikayesi (This is Us).

90’lı yılların sonlarında tüm dünyayı etkisi altına alan Avrupa çıkışlı format programlar olarak bilinen reality programlar küresel düzeyde bir uyarlama furyasına sebep oldu. Format belli bir ülkede üretilip yayınlanan başka ülkelerde yeniden üretilebilecek program şablonudur. Bu doğrultuda, bu programların alım satımı muazzam bir ticari boyuta ulaştı. Bu büyüme aslında televizyon endüstrisinin teknolojik ve yapısal değişimlerinin de sonucu olan yepyeni bir dönemin kapılarını açtı. Öte yandan, çeşitli sebeplerden dolayı uyarlama modası televizyon dizileri özelinde çok daha sonra başladı. Bunun en önemli sebebi olarak komedi ve drama gibi televizyon dizlerinin kültürel anlamda hassas sayılabilecek ögeler içermesi ve uyarlanma sürecinin reality programlara göre çok daha zor olması gösterilebilir. Bir televizyon dizisinin yeni bir ülkeye uyarlandığında, başarılı olabilmesi için seyircide bir olumlu karşılık bulması gerekmektedir. Uyarlanan dizinin başarılı olabilmesi seyircinin bu yeni versiyonda kültürel yakınlık bulabilmesine bağlıdır. Bu tezin temel teorik çerçevesi, Türkiye televizyonlarına uyarlanan Anne (Mother) ve Bir Aile Hikayesi (This is Us) dizilerinin incelenmesinde pek çok kavramı da içinde barındıran kompleks bir kavram olan kültürel yakınlığa dayanmaktadır. Kültürel yakınlık uyarlama bir diziyi seyircinin gözünde daha anlamlı ve daha yakın hale getiren belli başlı ögelere odaklanırken, gözden kaçan ya da odaklanılmayan başka etkenler de dizinin uyarlanış sürecinde belirleyici olabilmektedir. Bu tez kültürel yakınlık kavramın dayandığı noktaları ve ayrıca göz ardı ettiği ögeleri bütüncül olarak hesaba katarak Japon dizisi Mother’dan uyarlanan Anne ve Amerikan dizisi This is Us’tan uyarlanan Bir Aile Hikayesi isimli dizileri analiz etmektedir.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2019
Keywords: TV series; TV audiences; Adaptation; Cultural proximity; Anne (Mother); Bir Aile Hikayesi (This is Us); Televizyon dizileri; Televizyon seyircisi; Uyarlama; Kültürel yakınlık